How does the space of production wells influence the heat extraction efficiency?–defined by a 3D modeling work in enhanced geothermal system (EGS) - Wang, Ziwei; Zhang, Bo; Zhu, Xiaoyi; Yang, Liming; Fan, Yifan; Yin, Hongmei; Zhao, Peng; Liu, Jun (Frontiers in Energy Research, 2024)
The space of production well plays a crucial role in the heat extraction performance of the Enhanced Geothermal System (EGS), which have the potential to meet the growing global energy demand as a reliable energy source. Nonetheless, there has been insufficient research and attention focused on comprehending the impact of the space of production well on the efficiency and effectiveness of EGS. In this work, a series of numerical simulations were conducted to assess the impact of the space of production well on heat extraction efficiency in EGS. Three different cases were considered: Case 50 with 50 m production well spacing, Case 100 with 100 m production well spacing, and Case 150 with 150 m production well spacing. At the X-Y plane and Y-Z plane, the simulation results indicated that there were slight differences in temperature variation among the Case 50, Case 100 and Case 150. And the cooling area decreasing as the spacing of production wells decreased. Moreover, the delivery of cooling water via the injection well and its subsequent distribution to various reference points lead to a decline in temperature at each point, albeit with varying degrees of variation. Besides, the established efficiency (ef) for Case 50 is smaller than the Case 100 and Case 150 during the last 15 years. These findings contribute valuable insights to the exploration and exploitation of EGS systems and can serve as a guide for further research in this field.